SAT0288 Quality of life in patients with systemic lupus eriythematosus. (15th June 2017) - Voicu, G; Groseanu, L; Abobului, M; Vlad, V; Berghea, F; Predeteanu, D; Bojinca, V; Saulescu, I; Borangiu, A; Daia, S; Mazilu, D; Balanescu, A; et al.
Abstract : Background: The Quality of life (QoL) in patients with SLE is deeply affected by multiple factors including psychological and physical factors, the functional status and the general perception over health. Objectives: Evaluation of Quality of life and the perceptions over the disease in patients with SLE.functional status and the general perception over health. Methods: This is a 10 month prospective, cross-sectional study performed on 52 patients hospitalized diagnosed with SLE according to SLICC 2012 criteria. There were evaluated demographic data, organs manifestations, disease activity scores (SLEDAI, SLICC) and treatment. To evaluate the QoL several questionnaires were performed: Health Assessment Questionnaire (HAQ), EuroQol five dimensions questionnaire (EQ5d), Illness Perception Questionnaire and SF-36. Results: All patients were women with the mean age 49 years with a mean durations of illness 136 month (14). The mean SLEDAI – 5, 52 (5, 37) and SLICC – 2, 25 (1, 71). The mean HAQ value was 0, 83 (0, 81). The HAQ score doesn't correlate with SLICC (p=0, 461) and with SLEDAI (p=0, 172), but it was correlated with the neuropsychiatric manifestations. So the psychiatric affectation influences performing the usually daily activities (p=0, 005). When assessing Illness Perception Questionnaire, patients considered their life seriously affected by pain, mean value 6, 3 (2, 6), 72% consider the illness will be present for the rest of their lives, 90% appreciate that treatment is improving the QoL mean 9, 3 (1, 3), 68% consider to have many severe symptoms, more than 80% patients consider themselves preoccupied for their illness, more than 70% are emotionally affected by their illness and 48% consider stress being the main determinant factor of their illness. Questionnaire EQ-5d: 10% must stay in bed due to the disease, 8, 33% can not wash or dress themselves, 12, 5% are unable to perform usual daily activities, 62% experience pain or a moderate uncomfortable state and 65% are worried and or depressed. Cardio-vascular manifestations are correlated with diminished mobility (p=0, 002) leading to deficiency in self care (p=0, 002)also correlated with renal (p=0, 034) and psychiatric (p=0, 022) manifestations. Psychiatric manifestations also affect usual daily activities (p=0, 05). Age is correlated with pain and uncomfortable state (p=0, 004) but the responses to this item of EQ5D are not correlated with organ affectation, biological modification or disease activity scores. The presence of cutaneous manifestations is correlated with anxiety and depression (p=0, 02). Based on SF36 when calculating the mean value on each category was observed all the 8 categories affected - smallest values at physical role (37, 32) and general health (34, 21), less influenced part being the social function (51, 32).None of this items of SF 36 is correlated with SLICC or SLEDAI. Conclusions: SLEDAI as well as SLICC or specific organ involvement give no indications over the patients QoL, which must be assessed by performing HAQ and SF 36. References: Lupus. 2016 Mar 16. pii: 0961203316638934. [Epub ahead of print]Gender differences in systemic lupus erythematosus concerning anxiety, depression and quality of life.Macêdo EA1, Appenzeller S2, Costallat LT2. Disclosure of Interest: None declared